The only way is ethics: methodological considerations for a working-class academic. Issue 2 (2nd April 2020) - McInch, Alex
ABSTRACT: Ethnography as a methodological approach presents the fieldworker with many ethical crossroads throughout the research process. This is because of the unique position that ethnographers find themselves in, the environments that they research and the relationships which are formed. This paper presents four confessional vignettes from a broader ethnographic research project that illuminate the underside of fieldwork, and how the author dealt with a number of difficulties and dilemmas in the field as a working-class academic. Fieldwork was undertaken in a Welsh (UK) secondary school for one full academic year, and the paper argues that researcher identity must be remain fluid so that successful field relations are established and maintained. The paper concludes that researchers must think intersectionally about their endeavours and to also consider how one's own social baggage might impact upon the research process.